The cosmic conflict: Jesus against the devil in the letter to the church in Smyrna (Rev 2:8-11) - Kuryliak, Bohdan (Scottish journal of theology, 2025)
Scholars studying cosmic conflict in the book of Revelation primarily focus on chapters 12-14, while the letters to the seven churches are often overlooked. In this article I demonstrate the presence of key elements of cosmic conflict in the letters to the seven churches, with a particular focus on the letter to the church in Smyrna (Rev 2:8-11). I identify the main facets of spiritual warfare, such as Jesus Christ versus the devil; Christians versus Jews/Romans; and victory/life versus defeat/death. I conclude that this passage contributes to the military narrative of cosmic conflict in the Apocalypse.